Pelatihan Pembuatan Briket Arang Kayu Bus dan Pelatihan Penggunaan Kompor Briket Untuk Kebutuhan Rumah Tangga - Bako, Rahab M; Yusman, Nujannah (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
Conventional fuels such as kerosene, whose prices continue to increase and firewood is increasingly scarce, will cause many residents to experience difficulties in meeting their energy needs, both for their daily needs and for business needs. Daily cooking needs require a sufficient supply of fuel, such as kerosene, or firewood. The need for kerosene in a month is ± 30 liters, but its availability is often scarce, and when it is rare for retailers to sell it at multiple prices, this condition makes it even more difficult for people to meet their fuel needs. A service program to help provide solutions due to the scarcity of kerosene fuel. Training on making bus wood charcoal briquettes and training on the use of briquette stoves for household needs in Kamundu sub-district, Merauke, is very helpful for housewives (OAP) in making alternative fuels in the form of charcoal briquettes made from bus wood and also how to do it. using charcoal briquettes as fuel. After the training was held, we conducted monitoring regarding the making of bus wood charcoal briquettes by housewives (OAP) which they would then use as an alternative to kerosene fuel for their household needs.